Social Collectives: A Partial Form of Organizing that Sustains Social Innovation - Crespin-Mazet, Florence; Goglio-Primard, Karine; Grenier, Corinne (Management international / International Management / Gestiòn Internacional, 2017)
We mobilize the organizational and practice-based literature to determine the mechanisms enabling a social collective to introduce innovation in public rescue. The case highlights how this collective acquired characteristics of a partial organization by: (1) emergent characteristics reacting to critical incidents, (2) an overarching agenda supporting actors participation, (3) complementarity of exclusion and inclusion membership practices to enforce collective identity and reach a critical mass, (4) recognition of collective actorhood through reification practices, (5) the role of a secretariat through theorizing and developing close but discrete relationships with an external actor with critical expertise and resources.